Materi Pendidikan dalam Kitab Durrat al-Nâshihîn Karya Al-Khaubawy - Yamin, Mohamad; Manshur, Fadlil Munawwar (Tsamratul Fikri | Jurnal Studi Islam, 2017)
The book of Durrat al-Nâshihîn by Uthman bin Hasan bin Ahmad al-Syakir Al-Khaubawy is a very popular and controversial book. This book is considered important in the educational discipline because it contains educational materials and methods that may still be relevant to current contemporary Islamic educational practices. Although the book was written hundreds of years ago, the significance of the materials and methods on how the materials are poured or presented is believed to be relevant. The results of this study indicate that the Book of Durrat al-Nâshihîn contains 75 pieces of discussion material topics, including repeated discussions. Of the 75 topics, the discussion can be grouped into three educational materials, namely education of faith, religious education, and moral education. The content of aqidah education is more directed towards the education of beliefs and beliefs, especially those related to the shahada, the prophet of the Prophet, the belief in life after death, the end of the world with the awesomeness, the human deeds, and the belief in heaven and hell as a reward for those who do good or bad. The subject of worship education leads more to the education of servant devotion to God through religious practices that aim to always remember Him. These religious education materials include the fadhilah of fasting and the month of Ramadan, praying, dhikr, reading the Qur'an, patience, and other deeds. The material content of the moral education field is more directed to the problem of relationships among people in social life, which includes the virtue of friends, help-help, slander prohibition, ghibah, drinking, prohibition on actions that can damage the brotherhood, and what should be done and what everyone needs to shun.